2004
DOI: 10.1074/jbc.m308156200
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the Mu Transpososome Active Sites during a Cooperative Transition between DNA Cleavage and Joining

Abstract: Transposition of mobile genetic elements proceeds through a series of DNA phosphoryl transfer reactions, with multiple reaction steps catalyzed by the same set of active site residues. Mu transposase repeatedly utilizes the same active site DDE residues to cleave and join a single DNA strand at each transposon end to a new, distant DNA location (the target DNA). To better understand how DNA is manipulated within the Mu transposase-DNA complex during recombination, the impact of the DNA immediately adjacent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Previous studies suggested that MuB allosterically activates MuA. 20,23,38 Our new data extend these studies and support a model in which MuB functions to influence the conformational state of the transpososome in a concerted manner. Thus, we hypothesize that by favoring joined complexes, MuB acts both to stimulate strand transfer and to inhibit disintegration using a common mechanism.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies suggested that MuB allosterically activates MuA. 20,23,38 Our new data extend these studies and support a model in which MuB functions to influence the conformational state of the transpososome in a concerted manner. Thus, we hypothesize that by favoring joined complexes, MuB acts both to stimulate strand transfer and to inhibit disintegration using a common mechanism.…”
Section: Discussionsupporting
confidence: 75%
“…MuB promotes a cooperative change to influence the activity of the Mu transpososome Previous experiments 20,23,26,37 together with the analysis presented above reveal that MuB is a multifaceted activator of MuA and that it is especially important in driving the recombination reaction forward to the final strand transfer complex. To understand how MuB functions to control the activity of the transpososome, we sought to determine if it makes preferential contacts with specific MuA subunits within the transpososome.…”
Section: The Mub Activator Promotes Joining and Antagonizes Reversalmentioning
confidence: 91%
“…Formation of the Mu transpososome and progression of the complex through the various reaction stages are accompanied by a series of conformational changes resulting in successive increases in transpososome stability (see Mizuuchi and Mizuuchi 2001;Chaconas and Harshey 2002;Goldhaber-Gordon et al 2002a,b;Kobryn et al 2002;Yanagihara and Mizuuchi 2003;Williams and Baker 2004). Some changes in the Mu A monomer structure were apparent upon tetramerization, as noted by comparison (Fig.…”
Section: Catalysis In Transmentioning
confidence: 87%
“…The ATPase activity of MuB is stimulated by DNA and MuA. MuB not only captures target DNA and delivers it to the transpososome, but its interactions with MuA optimize all stages of transpsosome assembly (9, 3436) (Fig. 4).…”
Section: Transpososome Assembly Activity and Structurementioning
confidence: 99%
“…4A, B) (39, 45, 47). MuB stimulates assembly on both plasmid and oligonucleotide substrates; the stimulation is independent of presence of the FD on oligonucleotide substrates (36). …”
Section: Transpososome Assembly Activity and Structurementioning
confidence: 99%